Fatigue among breast cancer patients - Rzepka, Katarzyna; Nowicki, Andrzej (Contemporary Oncology/Współczesna Onkologia, 2010)
Fatigue along with pain, nausea and vomiting is one of the most prevalent symptoms among breast cancer patients. It is experienced by a greater number of breast cancer patients than any other symptom and it is perceived as a highly disruptive condition, resulting in functional impairment and affecting quality of life. Specific mechanisms causing fatigue remain unknown. The aetiology of fatigue is believed to be multifactorial. Identification of the reasons behind occurrence of fatigue among cancer patients is essential in order to define an effective treatment and intervention strategy. For measuring purposes, specific tools, facilitating the precise assessment of fatigue intensity, were developed. Comprehensive analysis should not only assess intensity of fatigue, but also define its impact on daily activity and identify presumable causes of fatigue. There are pharmacological strategies of fatigue treatment available, but the significance and value of the pharmacological approach have not been thoroughly examined yet. Education, counselling, physical exercises, energy conservation and management, sleep therapy and proper diet are recommended as non-pharmacological intervention strategies.